2018
DOI: 10.1088/1367-2630/aaa382
|View full text |Cite
|
Sign up to set email alerts
|

Charged dopants in neutral supercells through substitutional donor (acceptor): nitrogen donor charging of the nitrogen-vacancy center in diamond

Abstract: Charged defects are traditionally computed by adding (subtracting) electrons for negative (positive) impurities. When using periodic boundary conditions this results in artificially charged supercells that also require a compensating background charge of the opposite sign, which makes slab supercells problematic because of an arbitrary dependence on the vacuum thickness. In this work, we test the method of using neutral supercells through the use of a substitutional electron donor (acceptor) to describe charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Extensive tests showed that if the defects are placed at least 7.5 Å far from each other then the degeneracy of the corresponding orbitals is maintained and the constant shift in the KS levels can be well monitored and corrected 117 . In a recent study, the pair of NV center and ionized N s was analyzed in detail with arriving the same conclusion that 7.5 Å distance between the two defects suffices to avoid the splitting of the degeneracy of the corresponding orbitals, and NV center can be well approximated as isolated 166 . These achievements makes possible to directly simulate NV center with correct total energies that is necessary for modeling direct interaction of NV center with surface species 117 .…”
Section: B Diamond Surfacementioning
confidence: 96%
“…Extensive tests showed that if the defects are placed at least 7.5 Å far from each other then the degeneracy of the corresponding orbitals is maintained and the constant shift in the KS levels can be well monitored and corrected 117 . In a recent study, the pair of NV center and ionized N s was analyzed in detail with arriving the same conclusion that 7.5 Å distance between the two defects suffices to avoid the splitting of the degeneracy of the corresponding orbitals, and NV center can be well approximated as isolated 166 . These achievements makes possible to directly simulate NV center with correct total energies that is necessary for modeling direct interaction of NV center with surface species 117 .…”
Section: B Diamond Surfacementioning
confidence: 96%
“…Comparing the bulk conversion values for the different terminations (HSE06 computations), we get a value of 1.961 eV for the F-terminated surface (average value of the two configurations in the 15th layer), for the H/O/ OH-terminated surface we get 1.959 eV (for the configuration in the 15th layer), and for the N-terminated surface we get 1.963 eV (for the configuration in the 14th layer). This can be compared to the bulk value of 1.962 eV for a 512 atom neutral supercell (containing a NV-center and an electron donor nitrogen atom placed 12.23 Å from the NV-center along the symmetry axis of the supercell in the NV-N configuration) in our previous work [45]. As can be seen, the values are very close to each other, deviating 0.004 eV at most.…”
Section: N-terminated Surface-zpl (Hse06)mentioning
confidence: 61%
“…At least when the surfaces are defect free and without its own spin-density. It is also worth reiterating that the donor-N has no spin density at all [45], which is also verification of the success of the charging of the defect-center resulting in a neutral supercell.…”
Section: Bulk Conversion Depth For the Spin-densitymentioning
confidence: 69%
See 2 more Smart Citations